Water Quality Assessment of Sirsiya River - Shah, Binod Prasad; Pant, Bhoj R (Nepal Journal of Science and Technology, 2013)
The parameters such as temperature, PH, TSS, TDS, ammonia, phenol, cyanide, sulfide, oil and grease, chloride, DO, COD and BOD were taken to assess the water quality of Sirsiya river, central southern Nepal. Water samples were collected from upstream to downstream from the point receiving industrial effluent to Sirsiya river. It receives wastewater burden of more than 250 industries along Bara/Parsa industrial corridor. All the parameters except oil and grease were found within the generic standard. The study revealed that the physic-chemical characteristic of the river water was changing as a result of the discharge of untreated effluents from different industries. This may impact on water quality of Sirsiya river and also pose human health problems. Nepal Journal of Science and Technology Vol. 13, No. 2 (2012) 141-146 DOI: http://dx.doi.org/10.3126/njst.v13i2.7727